Structural analysis of historic construction. proceedings of the Sixth International Conference on Structural Analysis of Historic Construction, 2-4 July, Bath, United Kingdom /: proceedings of the Sixth International Conference on Structural Analysis of Historic Construction, 2-4 July, Bath, United Kingdom. Preserving safety and significance. Volume 1 : (2008) - Unknown
No abstract available